Virus - Curtis, Jamie Lee 1958-; Baldwin, William 1963-; Sutherland, Donald 1935-; Bruno, John; Hurd, Gale Anne; Pfarrer, Chuck; Feldman, Dennis (Viva Video, 1999)
Seeking refuge in the eye of a violent typhoon aboard an abandoned Russian military vessel, the crew of a crippled salvage tug encounters an alien life form holding the ship hostage that not only feeds off electricity, but thrives on developing new ways of killing the "virus" on Earth known as man.